2021
DOI: 10.37640/jim.v2i1.849
|View full text |Cite
|
Sign up to set email alerts
|

Studi Korelasi Motivasi Belajar terhadap Hasil Belajar Matematika Selama Daring

Abstract: The purpose of this study was to determine how much the relationship between learning motivation and learning outcomes online mathematics at SMP N 3 Wates. This research includes research with a quantitative approach and the type of research is ex post facto because it does not provide treatment to the research sample and the form of the relationship is a causal relationship. The population in this study were students of SMP N 3 Wates. The sampling technique was using cluster random sampling technique. The dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 11 publications
0
3
0
5
Order By: Relevance
“…Research by Wijayanti & Widodo (2021) concluded that there is a positive influence of learning motivation on learning outcomes. The higher the learning motivation, the better the achievement of learning outcomes, and vice versa; if the motivation is low, learning outcomes will also be low.…”
Section: Discussionmentioning
confidence: 99%
“…Research by Wijayanti & Widodo (2021) concluded that there is a positive influence of learning motivation on learning outcomes. The higher the learning motivation, the better the achievement of learning outcomes, and vice versa; if the motivation is low, learning outcomes will also be low.…”
Section: Discussionmentioning
confidence: 99%
“…Tidak hanya guru, terbatasnya interaksi dalam proses pembelajaran juga dikeluhkan oleh siswa [6]. Selain itu, siswa juga mengalami kendala lain dalam pembelajaran daring matematika yaitu kesulitan berkonsentrasi, penurunan motivasi, dan minat belajar [7]- [10].…”
Section: Pendahuluanunclassified
“…Berdasarkan penelitian yang dilakukan oleh Niken Bayu Argaheni menyatakan dalam penelitiannya terdapat dampak dari pembelajaran secara daring yang terjadi disebabkan penggunaan/penerapan belajar online ini masih membingungkan mahasiswa, mahasiswa kurang produktif, mahasiswa tidak aktif dalam belajar dan lebih cenderung menjadi pasif yang kurang kreatif sehingga menyebabkan mahasiswa mengalami stress akan pembelajaran yang memiliki tugas banyak (Argaheni, 2020). Seiring juga dengan hasil penelitian yang dilakukan oleh Nisa Wijayanti yang menyatakan bahwa didapatkan hasil dari pengolahan analisis data terkait hubungan antara motivasi belajar dengan hasil belajar yaitu sebesar 0,386 dengan koefisien korelasi sebesar 14,5% dengan kategori rendah (Wijayanti & Widodo, 2021). Sehingga dapat dinyatakan bahwa motivasi belajar saat belajar daring menimbulkan penurunan motivasi belajar.…”
Section: Hasil Dan Pembahasanunclassified